2004
DOI: 10.1001/archneur.61.11.1669
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Disorders in Severe Acute Respiratory Syndrome

Abstract: The neuromuscular problems in patients with SARS are considered to be critical-illness polyneuropathy or myopathy, possibly coexistent. Further pathological and microbiological studies are necessary to determine the relationship between SARS coronavirus and neuromuscular problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
410
1
25

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(448 citation statements)
references
References 17 publications
12
410
1
25
Order By: Relevance
“…However, the reduced exercise capacity after hospital discharge in SARS survivors could not be accounted for by impairment of pulmonary function alone, 12,13,18,19 whereas extra‐pulmonary causes such as physical deconditioning, muscle weakness and poor motivation were contributing factors. Several reasons for muscle weakness were suggested, including viral‐induced myositis at initial presentation, muscle wasting and deconditioning due to prolonged bed rest, steroid myopathy and critical illness‐associated poly‐neuropathy or myopathy 12,13,18,19,43 …”
Section: Discussionmentioning
confidence: 99%
“…However, the reduced exercise capacity after hospital discharge in SARS survivors could not be accounted for by impairment of pulmonary function alone, 12,13,18,19 whereas extra‐pulmonary causes such as physical deconditioning, muscle weakness and poor motivation were contributing factors. Several reasons for muscle weakness were suggested, including viral‐induced myositis at initial presentation, muscle wasting and deconditioning due to prolonged bed rest, steroid myopathy and critical illness‐associated poly‐neuropathy or myopathy 12,13,18,19,43 …”
Section: Discussionmentioning
confidence: 99%
“…The functional disability appears out of proportion to the degree of lung function impairment and may be due to extrapulmonary factors such as muscle deconditioning and steroid myopathy [145,146]. Critical-illness-associated polyneuropathy/myopathy has also been observed in a few SARS survivors [147]. The reported incidence rates of avascular necrosis of bone among different cohorts in Hong Kong range from 4.7-15 % [124,148,149], whereas one study from Beijing reported a high incidence of 42 % [123].…”
Section: Long-term Outcomementioning
confidence: 99%
“…после выписки из стационара сохранялось снижение физической вы носливости, которое нельзя было объяснить только легочными функциональными нарушениями [27]. Снижение переносимости физических нагрузок у данных больных может быть связано не только с легочными функциональными параметрами, но также с экстралегочными факторами, такими как атрофия скелетных мышц (от бездействия), стероид индуцированная и вирусная миопатия, полиней ропатия / миопатия критических состояний [28], и с другими физиологическими причинами. Эти данные, конечно, отличаются от результатов настоя щего годичного наблюдения.…”
Section: Discussionunclassified